Debating Diseases in Nineteenth-Century Colombia: Causes, Interests, and the Pasteurian Therapeutics (2015)
This article explores the medical conceptualization of the causes of diseases in nineteenth-century Colombia. It traces the history of some of the pathologies that were of major concern among nineteenth-century doctors: periodic fevers (yellow fever and malaria), continuous fevers (typhoid fever), and leprosy (Greek elephantiasis). By comparing the transforming conceptualizations of these diseases, this article shows that their changing pattern, the idea of climatic determinism of diseases (neo-Hippocratism and medical geography), the weak standing of the medical community in Colombian society, as well as Pasteurian germ practices were all crucial in the uneven and varied reshaping of their understanding. © 2015, Johns Hopkins University Press. All rights reserved.